Nutritive value of three fodder species at different stages of maturity (Bangladesh Journal of Animal Science, 2013)
An experiment was conducted to compare the nutritive value of three fodder species: Para (Brachiaria mutica Stapf.), German (Echinochloa crusgalli L.) and Dhal (Hymenachne pseudointerrupta C. Muell) at three different stages of maturity. The grasses were cultivated in 9 plots arranged in completely randomized design having three replications for each fodder.  The area of each unit plot was 6 m x 6 m. Number of cuttings were 16,000 /hectare, where plant to plant distance was 16 cm and row to row distance was 16 cm. Equal amount of organic and chemical fertilizer were applied in all stages of maturity. The fodders were first harvested after 60 d of planting, second and third harvests were done after successive 60 d of re-growth. There was highly significant (p